Analysis Of Employee Service Quality Dimensions That Influence Customer Trust Of Tiki JNE Bekasi Services - Sutisna, Muhammad Ikhsan; Alim, Syahrul (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Service quality is one of the factors that influences the level of customer loyalty towards products or services. Increasingly strong competition will make business people more enthusiastic in providing service and trust to consumers with the aim of providing a sense of satisfaction to customers. With the rapid development of companies providing goods delivery services or courier services, many online shop sellers use these courier services. Having a courier service will make it easier for them to deliver ordered goods according to the type of package service they want. This research aims to determine the influence of service quality on consumer trust in JNE Bekasi tiki. There were 100 respondents in this research, namely JNE Bekasi consumers. This research is quantitative and uses SPSS analysis tools. From the data processing that has been carried out, it is known that physical evidence, reliability, guarantee, responsiveness and empathy partially have a positive and significant effect on consumer trust at JNE Bekasi.